THE ROLE OF BUSINESS ANALYTICS IN E-COMMERCE - Reddy, Jogannagari Malla; Prasad, S.V.A.V. (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
E-Commerce is a dynamic industry because of its rapidly changing technology. E-commerce performs a vital role in business phenomena in trading products and services. It provides extraordinary features in the business growth of the country's economy. E-Commerce firms are spending huge amounts of money on Data Analytics to extract actionable insights from larger datasets. Data-driven business insights are crucial for the E-Commerce sector to measure the changing market trends and consumer behavior. The business sector is grown-up to greater heights with the involvement of Data Analytics in E-Commerce. E-Commerce Analytics designed to analyze and predict the future trends of the market to attain a competitive advantage. However, E-Commerce may contain some critical challenges apart from the opportunities. This paper highlights the role of Data Analytics perceived as a value creator for the E-Commerce industry to attain competitive advantage.